Raising Of Polyclonal Antibody Against The Aspergillus Oryzae Proteins In Albino Rat - KAMARAJ.M; RAJESHWARI SIVARAJ; MUTHUSAMY GOVARTHANAN (International Journal of Pharma and Bio Sciences, 2012)
Aspergillus oryzae is one of the common plant pathogens in wheat, sorghum and other crops. Its toxic activity has been proved. Hence, a sensitive, rapid, and inexpensive screening test to detect Aspergillus in agricultural commodities is necessary to protect human health. Aspergillus oryzae proteins were prepared, characterized, and used as an antigen. 6-month-old white albino rat were immunized by the antigen in combination with Freund’s adjuvant. The antiserum of immunized rat was collected after 35 days. Proteins present in antiserum were precipitated by ammonium sulphate precipitation and purified by dialysis, ion exchange chromatography and SDS PAGE. Immuno blotting analysis was performed to determine antibody specificity towards the antigen. The optimum dilution of prepared IgG was 1:32. Dot strip ELISA test confirmed the presence of specific Antigen-Antibody interaction